Factors Affecting Farmer's Decision in Converting The Function of Agricultural Lands - Atika Fikri Tsani; Yunastiti Purwaningsih; Akhmad Daerobi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
This study aims to analyze the factors that affect farmer’s decision in converting the function of their agricultural lands. The factors are: farmer’s age, education level, total number of family members, the area of agricultural lands, income, and location of agricultural land. This study is conducted in Depok sub-district, Sleman district, Yogyakarta, as an area with high rate agricultural land function conversion, marked by the decrease in the area of agricultural land. This study is conducted using survey method, with farmers who decide to convert the function of their agricultural land and farmers who do not as unit analysis. The data is analyzed using logistic regression. The analysis result shows that farmer’s age and agricultural land location have negative effect on the decision to convertagricultural land function, education level and total numbers of family members have positive effect, and the area of agricultural lands and income have no significant effect on the decision to convert the function of agricultural lands